Murabaha Oriented at Sharia Banks in Kendari City - Rahmat Rahmat; Ernawati Ernawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The proportion of murabaha financing in sharia banking is more dominant than profit-sharing financing, so that Sharia banking behaves murabaha oriented. The study aims to determine whether the risk and the level of profit loss sharing financing have an effect on murabaha-oriented behavior in sharia banks. The research was conducted in Kendari City from January to April 2019 with four informants from the bank management. It is a descriptive quantitative research using percentage assistance. The results show that the risk factor for profit sharing financing is the most important consideration for sharia banks to choose murabaha financing, while the profit sharing rate received is a factor that is considered after the risk. The financing risk experienced by sharia banks in Kendari City is in the form of financing problems. Meanwhile, the profit sharing rate factor determines the murabaha oriented behavior which is driven by the lower rate of return for the results compared to murabaha financing.